Training needs assessment for leaders in nursing based on comparison of competency models - Kvas, Andreja (Organizacija (Kranj), 2014)
Background and Purpose: The main purpose behind the formation of leadership competency models must be the improvement of leadership. A competency model should serve as one of the tools for selecting the most suitable leaders, appraising their work, assessing training needs and preparing programmes of functional and formal education. The objective of this research is to assess the training needs of leaders in health care. A comparison of leadership competency models between different professional groups should serve as one of the tools with which to assess the training needs of various levels of leaders. Design/Methodology/Approach: A descriptive study using a survey design was conducted on 141 nurse leaders in Slovenia. Respondents indicated to what extent each of 95 different behaviours was characteristic of a person at their leadership level. Results: The most important competence dimensions (groups of behaviours) for leaders in health care are (1) at the first - top leadership level: strategic thinking, openness to change and responsibility; (2) for leaders at the second - middle leadership level: relations with co-workers, animation, resistance to stress; and (3) for leaders at the third leadership level: realisation skills, execution of procedures, communication. Training needs assessments were done for three leadership levels in nursing care. Conclusions: The greatest need for training of nurse leaders can be observed at the third leadership level. Special training programmes should be organised in the competency areas of realisation skills, execution of procedures, communication, education and ethics.
Keywords: zdravstvena nega; vodenje; kompetence; strokovno izobraževanje; poklicno usposabljanje; Slovenia; Slovenija